Monologues, dialogues and common priors - Alfredo Di Tillio; Ehud Lehrer; Dov Samet (Theoretical Economics, 2022)
The main purpose of this paper is to provide a simple criterion enabling to conclude that two agents do not share a common prior. The criterion is simple, as it does not require information about the agents' knowledge and beliefs, but rather only the record of a dialogue between the agents. In each stage of the dialogue the agents tell each other the probability they ascribe to a fixed event and update their beliefs about the event. To characterize dialogues consistent with a common prior, we first study monologues, which are sequences of probabilities assigned by a single agent to a given event in an exogenous learning process. A dialogue is consistent with a common prior if and only if each selection sequence from the two monologues comprising the dialogue is itself a monologue.
Keywords: D83; 330; Learning processes; Bayesian dialogue; Bayesian monologue; Ratio variation; Joint fluctuation; Agreement